1993
DOI: 10.1002/gepi.1370100305
|View full text |Cite
|
Sign up to set email alerts
|

Segregation analysis of autosomal dominant polycystic kidney disease

Abstract: The results of classical segregation analysis on 159 families with polycystic kidney disease (PKD) are presented. It had been previously estimated that about 95% of autosomal dominant PKD (ADPKD) families have PKD1, the gene localized to chromosome 16p. The main purpose of the study was to determine if PKD shows any segregation distortion and to obtain new estimates of the age-dependent penetrance. Penetrance at the early ages of onset has increased during the last decade, presumably because of improvements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 11 publications
1
8
1
Order By: Relevance
“…Our study cohort represents a typical sample of families with ADPKD seen in the clinic; however, we observed a higher proportion of our Canadian families affected with PKD2 compared with two studies of linkage-characterized European families from the late 1980s to early 1990s (26 versus 15%, respectively). 6,7 Our finding is consistent with a recent populationbased study from Olmsted County, MN, which reported a prevalence of PKD2 of 36%. 18 Given that PKD2 is milder and may be underdetected before the era of widespread ultrasound screening, the two more recent studies suggest that its prevalence may be higher than previously estimated.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study cohort represents a typical sample of families with ADPKD seen in the clinic; however, we observed a higher proportion of our Canadian families affected with PKD2 compared with two studies of linkage-characterized European families from the late 1980s to early 1990s (26 versus 15%, respectively). 6,7 Our finding is consistent with a recent populationbased study from Olmsted County, MN, which reported a prevalence of PKD2 of 36%. 18 Given that PKD2 is milder and may be underdetected before the era of widespread ultrasound screening, the two more recent studies suggest that its prevalence may be higher than previously estimated.…”
Section: Discussionsupporting
confidence: 82%
“…Mutations of PKD1 and PKD2 are thought to account for 85 and 15% of cases, respectively, in linkage-characterized European populations. 6,7 Although the clinical manifestations overlap completely between two gene types, there is a strong locus effect on renal disease severity. Patients with PKD1 have significantly more severe renal disease than patients with PKD2, with larger kidneys and earlier onset at ESRD (median age 53.4 versus 72.7 yr, respectively).…”
mentioning
confidence: 99%
“…For example, Dobin et al (1993) reported that age at detection was normally distributed with mean 20 years and standard deviation 15.94 years, lower than in previous studies (Dalgaard 1957;Bear et al 1984). The age of full clinical penetrance in Dobin et al (1993) is 58, almost the same as in Dalgaard (1957).…”
Section: A3 Prognosismentioning
confidence: 45%
“…1999). Dobin et al (1993) estimated the penetrance to the development of detectable cysts to be over 70% by age 30, over 95% by age 50, and 99% by age 55. c. The development of symptoms (commonly urinary tract infection, haematuria, hypertension, loin pain, and gastrointestinal complications). Most sufferers develop symptoms in their third or fourth decade of life.…”
Section: Appendix Adult Polycystic Kidney Disease A1 General Featuresmentioning
confidence: 99%
“…Mutations of two genes, PKD1 (MIM 601313) and PKD2 (MIM 173910), respectively, account for approximately 85 and 15% of cases in the white population (6,7). The existence of a rare third gene for ADPKD has been suggested by the reports of several families who are unlinked to both known gene loci (8 -12).…”
mentioning
confidence: 99%